2022
DOI: 10.1002/jbm4.10631
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Single‐Cell RNA‐Seq Analysis Reveals the Novel Trajectory of Osteoclast Differentiation and Therapeutic Targets

Abstract: Bone turnover is finely tuned by cells in the bone milieu, including osteoblasts, osteoclasts, and osteocytes. Osteoclasts are multinucleated giant cells with a bone-resorbing function that play a critical role in regulating skeletal homeostasis. Osteoclast differentiation is characterized by dramatic changes in morphology and gene expression following receptor activator of nuclear factor-kappa-Β ligand (RANKL) stimulation. We performed single-cell RNA-sequencing analyses of human and murine osteoclast-lineage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 41 publications
3
25
1
Order By: Relevance
“…0.3.4 ( 19 ) were used in the integrative analysis of conventional scRNA-seq and iscRNA-seq. Four datasets of scRNA-seq,GSM4419695 (post RANKL stimulation day 0), GSM4419699 (day 1), GSM4419703 (day 3) by Dr. Tsukasaki ( 20 ), and published undeposited data (day 4) by Dr. Omata ( 21 ) were included. Before merging datasets, entrez IDs were transformed to gene symbols with EnsDb.Mmusculus.v79 ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…0.3.4 ( 19 ) were used in the integrative analysis of conventional scRNA-seq and iscRNA-seq. Four datasets of scRNA-seq,GSM4419695 (post RANKL stimulation day 0), GSM4419699 (day 1), GSM4419703 (day 3) by Dr. Tsukasaki ( 20 ), and published undeposited data (day 4) by Dr. Omata ( 21 ) were included. Before merging datasets, entrez IDs were transformed to gene symbols with EnsDb.Mmusculus.v79 ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
“…Conventional scRNA-seq has already been applied for in vitro Osteoclast culture ( 4 ). Our group had described the difference in the OC differentiation pathway between human and mouse ( 5 ). However, conventional Sc techniques does not allow the separation of OCs into Scs due to their large size and fragility.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first article by Fujii and colleagues, ( 1 ) the authors identified a novel “surgery‐induced” highly inflammatory CD9 + IL1 + macrophage population in a mouse model of anterior cruciate ligament reconstruction surgery, which resolved early and became replaced by another type of macrophages. In the second article by Omata and colleagues, ( 2 ) the authors identified a GTPase family member, RAB38, as a highly expressed molecule in both human and murine osteoclast precursor cells. This protein was associated with dynamic changes in histone modification and transcriptional regulation.…”
mentioning
confidence: 99%